Improvement Mathematical Concept Understanding of High School Student Through Problem-Based Learning Model Assisted by Quizizz - Nurfadhilah, Tiara Rossa; Putra, Beni Yusepa Ginanjar; Rohimah, Siti Maryam (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2025)
This study aims to see the improvement of high school students' mathematical concept understanding through the Problem-Based Learning (PBL) model with the help of Quizizz. The method used is quasi-experiment with nonequivalent control group design. The subjects of this study were grade X students in one of the high schools in Bandung Regency consisting of two classes, namely class X-H as the control class and class X-I as the experimental class, each totaling 36 students. The research instrument was a description test of mathematical concept understanding. The results showed that the improvement in the ability to understand the mathematical concepts of students who used the PBL model with the help of Quizizz was higher than students who used the PBL model.